2017
DOI: 10.1503/cjs.010016
|View full text |Cite
|
Sign up to set email alerts
|

Long-term use of left ventricular assist devices: a report on clinical outcomes

Abstract: Background:The literature examining clinical outcomes and readmissions during extended (> 1 yr) left ventricular assist device (LVAD) support is scarce, particularly in the era of continuous-flow LVADs. Methods:We completed a retrospective cohort study on consecutive LVAD patients from June 2006 to March 2015, focusing on those who received more than 1 year of total LVAD support time. Demographic characteristics, clinical outcomes and readmissions were analyzed using standard statistical methods. All readmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…(1) Despite the widespread adoption and success of LVADs for bridge-to-transplant or destination therapy indications, several attendant complications continue to limit the efficacy of LVADs. (2,3) The prevention and management of certain complications such as bleeding, hemolysis, stroke and driveline infections has fortunately improved, particularly with the newer generation LVADs. (4-7) Conversely, postoperative right ventricular failure (RVF) has persisted as a perennial vexing challenge to LVAD success.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Despite the widespread adoption and success of LVADs for bridge-to-transplant or destination therapy indications, several attendant complications continue to limit the efficacy of LVADs. (2,3) The prevention and management of certain complications such as bleeding, hemolysis, stroke and driveline infections has fortunately improved, particularly with the newer generation LVADs. (4-7) Conversely, postoperative right ventricular failure (RVF) has persisted as a perennial vexing challenge to LVAD success.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that thrombosis and thromboembolic events can occur in up to 20% of patients with an LVAD. 15 Pump thrombosis may cause pump output reduction and even device malfunction, stroke, and thromboembolic events, which expose patients to the risk of sudden death and can necessitate pump-exchange surgery. Although antithrombotic strategies have been adopted to prevent pump thrombosis, the partial efficacy is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical outcomes for LVAD implantation have been extensively reviewed (see for example [10,61,74,75]) including for infection. It is estimated that 15% of LVAD recipients die due to infectious complications, with the majority of deaths occurring within the first 30 days of receipt [76].…”
Section: Outcomes In Lvad Infectionsmentioning
confidence: 99%